Self-Paced Training Kit (Exam 70-640) : Configuring Windows Server 2008 Active Directory - Holme, Dan; Ruest, Danielle (Washington Microsoft Press, 2011)
Contents: creating an Active Directory Domain; administering Active Directory Domain services; administering user accounts; managing groups; configuring computers accounts;...
Includes bibliographical references and index
Keywords: Công nghệ thông tin